Direct Catalytic Anti-Markovnikov Addition of Carboxylic Acids to Alkenes - Perkowski, Andrew J. (2013)
A direct catalytic anti-Markovnikov addition of carboxylic acids to alkenes is reported. The catalyst system is comprised of the Fukuzumi acridinium photooxidant (1) and a substoichiometric quantity of a hydrogen atom donor. Oxidizable olefins such as styrenes, trisubstituted aliphatic alkenes, and enamides can be employed along with a variety of carboxylic acids to afford the anti-Markovnikov addition adducts exclusively. A deuterium-labeling experiment lends insight to the potential mechanism.